Efficient synthesis of gamma-valerolactone-a potential fuel from biomass derived levulinic acid using catalytic transfer hydrogenation over Hf@CCSO3H catalyst - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2020)
A new hafnium based carbonaceous catalyst (Hf@CCSO3H) was prepared by simultaneous carbonization and sulfonation of readily available glucose, followed by incorporation of hafnium metal on the surface of catalyst. The catalyst was well characterized using FT-IR, PXRD, EDX, SEM, C-13 CPNMR, XPS and BET analysis. The catalytic activity of Hf@CCSO3H was evaluated for synthesis of gamma-valerolactone-a potential fuel and green solvent. gamma-valerolactone was synthesized from biomass derived levulinic acid by catalytic transfer hydrogenation using 150 wt% of catalyst at 200 celcius for 24 h in isopropanol solvent as a hydrogen donor. 100% conversion of levulinic acid was achieved with an excellent yield of 96% with more than 99% selectivity of gamma-valerolactone as evident from GC analysis. The method developed is simple, efficient and economical. [GRAPHICS] .
Keywords: gamma-Valerolactone; Hydrogenation; levulinic acid; Transfer